The development of a baculovirus expression system for the production of Helicoverpa armigera stunt virus capsids for use in the encapsidation of foreign molecules - Mosisili, Kekeletso Mpho Thakane (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2003)
The capsid protein of Helicoverpa armigera stunt virus (HaSV) a T=4 insect virus was expressed in Spodoptera frugiperda 9 cells using a baculovirus vector. When the insect cells were infected at a high MOl the expressed coat protein assembled into virus-like particles (VLPs) that spontaneously underwent maturation and were morphologically indistinguishable from wild-type HaSV. The VLPs were electron dense when viewed under EM and encapsidated their coat protein mRNA. When Sf9 cells were infected at a low multiplicity of infection (MOl) the expressed capsid protein assembled into procapsids that did not spontaneously undergo maturation. These procapsids underwent autoproteolytic maturation cleavage when they were treated with an acidic buffer. The procapsids were used in the encapsidation of a FITC labelled peptide. The peptide encapsidating VLPs showed an increase in their buoyant density that was not collaborated by an increase in the concentration of the FITC labelled peptide detected when these samples were compared to control samples with similar buoyant densities.
Keywords: Helicoverpa armigera; Fall armyworm; Baculoviruses; Insects -- Viruses; RNA -- Analysis